Assessment of 3D modeling for rotor–stator contact simulations. (29th September 2015) - Tannous, Mikhael; Cartraud, Patrice; Torkhani, Mohamed; Dureisseix, David
Abstract: Most often the dynamic analysis of rotor-to-stator rub is performed using 1D models. This leads to a small computational cost, but the reliability of the results is difficult to assess. This research work compares and analyzes the results of 1D and 3D rotor–stator contact problems, for different contact conditions more and less severe. The rotor vibrations are due to rotating imbalance at a given constant rotating speed. In this paper, it is shown that regarding the rotor orbits, the 3D and 1D models responses are very close. However, using a 3D model improves the simulation results. The 1D model actually suffers from limitations resulting from rigid-body displacement assumption of the rotor׳s cross-section, which originates approximations in the rotor-to-stator contact modeling. Thus, the friction torque generated by the contact is overestimated in a 1D model. The 3D model, however, can present some local effects in the vicinity of the contact zone.